Enforcement of Minimum Legal Size on Fishers in Kerala, India: An Economic Appraisal - Meharoof, Mohammed; M., Rajeshwaran; S. Salim, Shyam; Wajahat Qureshi, Neha; Kumar Yadav, Vinod; Prakash, Swadesh (Fishery Technology, 2023)
The implementation of Minimum Legal Size (MLS) as a tool for managing fisheries and addressing the menace of juvenile fishing was first implemented by the state of Kerala in India in 2015. Since sustainability and profits offer a dramatic trade-off, the study has been conceptualized on the hypothesis that MLS has negatively affected the income of fishers. Primary data from 210 respondents across mechanized, motorized, and non-motorized fishing sectors were collected from six districts of Kerala to analyze and assess the change in income of fishers after the adoption of minimum legal size. The income of fishers who adopted MLS were found to be reduced in all the sectors viz. purse and ring seiners, single day trawlers, motorized gillnetters and non-motorized crafts with 4.04, 2.31, 2.14, and 1.48 per cent reduction in income respectively. The benefit-cost analysis between compliers and non-compliers of MLS revealed that the adoption of minimum legal size has not significantly affected the fishers, as they could fetch higher price for their catch which negated the loss of income due to MLS adoption. These results highlight the necessity of implementing management measures like MLS to achieve sustainability and better management of marine capture fisheries.